The Employment Status and Sense of Powerlessness in Communities Affected by Industrial Activities - Widiyawati, Wiwik; Laily , Nadhirotul; Sukaris, Sukaris; Mulyani, Endah; Widiharti, Widiharti; Sari, Diah Ratna (Journal of Nursing Science Update (JNSU), 2025)
Helplessness is a phenomenon that can impact individuals across all age groups, including both the young and the elderly. Specifically, adolescents and adults often experience feelings of helplessness due to their perceived limitations in accessing education, employment, and economic opportunities. This study employs a quantitative methodology with a cross-sectional design aimed at preventing the onset of psychological disorders among individuals residing in the industrially affected regions. Data collection was executed through a questionnaire distributed via Google Forms. The study's population comprised 1,580 individuals from the industrial area of Driyorejo District in Gresik Regency. A statistically significant p-value of 0.00 (p < 0.05) was obtained, demonstrating a correlation between feelings of helplessness and employment status. Furthermore, both internal and external factors contribute to the emergence of helplessness among civil servants. Therefore, governmental authorities must devise and implement strategies to mitigate mental health disorders that may arise among residents adversely affected by industrial operations.